Expatriate Managers: Effects on Firm Performance - Miklós Koren; Álmos Telegdy (CESifo GmbH, 2024)
Using a novel Hungarian dataset on firms and their Chief Executive Officers (CEOs), we estimate the impact of hiring expatriate CEOs. By examining foreign acquisitions where the new owner replaces the incumbent CEO with an expatriate or a local CEO, we address the selection into both acquisition and CEO hiring. Firms led by expatriate CEOs show 13 percent total factor productivity growth, 95 percent sales growth, and increase both exports and domestic sales. Hiring expatriate CEOs enhances firm performance in both international and domestic markets. Our findings suggest that expatriates have superior general management skills.
Keywords: F23; F61; L25; 330; expatriate CEO; foreign acquisition; firm performance; Hungary